Mexican Americans Receive Less Intensive Stroke Rehabilitation Than Non-Hispanic Whites - Morgenstern, Lewis B.; Sais, Emma; Fuentes, Michael; Ifejika, Nneka L.; Jiang, Xiaqing; Horn, Susan D.; Case, Erin; Lisabeth, Lynda D. (Stroke (1970), 2017)
Mexican Americans (MAs) have worse neurological, functional, and cognitive outcomes after stroke. Stroke rehabilitation is important for good outcome. In a population-based study, we sought to determine whether allocation of stroke rehabilitation services differed by ethnicity. Patients with stroke were identified as part of the Brain Attack Surveillance in Corpus Christi (BASIC) project, TX, USA. Cases were validated by physicians using source documentation. Patients were followed prospectively for 3 months after stroke to determine rehabilitation services and transitions. Descriptive statistics were used to depict the study population. Continuous baseline variables were compared using 2 sample tests or Wilcoxon rank-sum tests by ethnicity. Categorical baseline variables were compared using χ tests. Ethnic comparisons of rehabilitation services were compared using χ tests, Fisher's exact tests, and logistic regression. Seventy-two subjects (50 MA and 22 non-Hispanic white [NHW]) were followed. Mean age, NHW-69 (SD 13), MA-66 (SD 11) years, sex (NHW 55% male, MA 50% male) and median presenting National Institutes of Health Stroke Scale did not differ significantly. There were no ethnic differences among the proportion of patients who were sent home without any rehabilitation services ( =0.9). Among those who received rehabilitation, NHWs were more likely to get inpatient rehabilitation (73%) compared with MAs (30%), =0.016. MAs (51%) were much more likely to receive home rehabilitation services compared with NHWs (0%) ( =0.0017). In this population-based study, MAs were more likely to receive home-based rehabilitation, whereas NHWs were more likely to get inpatient rehabilitation. This disparity may, in part, explain the worse stroke outcome in MAs.